From Isolation to Integration : The Borderlands of the Horn of Africa - World Bank (World Bank, Washington, DC, 2020)
The World Bank Group's Horn of Africa Regional Initiative promotes resilience and economic opportunity in one of the world’s most challenging regions for security and development. Within the region, extreme poverty, vulnerability, fragility, and food insecurity are disproportionately concentrated in the arid and remote border regions. But despite its challenges, there are areas in the borderlands with real economic potential. For example, the region's international borders have long allowed communities to benefit from price differentials through licit and illicit trade (Scott-Villiers 2015). Pastoralism and trade, the dominant livelihoods in the Horn of Africa, require the easy movement of people and goods within and across borders—and continue to heavily rely on cross-country clan and ethnic affiliations. Local institutions therefore still play a key role in regulating and facilitating economic activity and managing conflict, especially as the formal institutions are often weak or absent. Even in areas at the periphery of state control, the borderlands remain highly connected to circuits of global capital and exchange.